2018
DOI: 10.1158/1055-9965.epi-18-0122
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Roles of Perioperative Body Mass Index and Weight Loss in the Long-Term Survival of Gastric Cancer Patients

Abstract: Most patients with gastric cancer rapidly lose weight after gastrectomy. Therefore, analysis of the effect of body mass index (BMI) on patients with gastric cancer survival should include postoperative BMI and BMI loss and preoperative BMI. This retrospective cohort study analyzed the effect of three BMI variables and their interaction on long-term outcomes. Preoperative BMI analysis included 2,063 patients with gastric cancer who underwent curative gastrectomy between January 2009 and December 2013 at Seoul N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…BMI distribution between stages was well balanced. Furthermore, we found that severe BMI loss (>10%) at one year after surgery was an independent risk factor for both OS and DFS, which was similar to previous reports that postoperative severe BMI loss (>4.5) (HR, 1.79; 95% CI, 1.29-2.50) was associated with higher mortality [16], and body weight loss ≥15% at 1 month after gastrectomy might lead to poor survival [24]. Compared to previous research that was limited to either one certain time point after gastrectomy or an uncertain wide time range, our study focused on 4 precise time points (pre, post_1m, post_6m, post_12m) and emphasized the importance of BMI dynamic monitoring.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…BMI distribution between stages was well balanced. Furthermore, we found that severe BMI loss (>10%) at one year after surgery was an independent risk factor for both OS and DFS, which was similar to previous reports that postoperative severe BMI loss (>4.5) (HR, 1.79; 95% CI, 1.29-2.50) was associated with higher mortality [16], and body weight loss ≥15% at 1 month after gastrectomy might lead to poor survival [24]. Compared to previous research that was limited to either one certain time point after gastrectomy or an uncertain wide time range, our study focused on 4 precise time points (pre, post_1m, post_6m, post_12m) and emphasized the importance of BMI dynamic monitoring.…”
Section: Discussionsupporting
confidence: 90%
“…Most patients who underwent gastrectomy and chemotherapy suffer body weight loss due to decreased food intake and medication-induced adverse effects [14]. Several retrospective cohort studies showed that the survival outcomes of overweight GC patients were superior to those of underweight GC patients [15,16], but some studies showed opposite results [17]. Most of the BMI data were measured at diagnosis, few studies have established the relationship between BMI dynamic changes upon therapy and long-term survival in GC patients, particularly in the Chinese population.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…we found that BMI ≥ 25 kg/m was risk factors to body weight loss during three months after gastrectomy in GC patients. However, the result was contract with the study by Park et al, who found that preoperative BMI < 23 kg/m were associated with severe weight loss after gastrectomy (Park et al 2018). Similar to previous studies (Davis et al 2016;Nishigori et al 2017;Segami et al 2018), we found that total gastrectomy was a risk factor for postoperative weight loss.…”
Section: Factors Contributed To Body Weight Change After Gastrectomysupporting
confidence: 89%
“…We found that BMI ≥ 25 kg/m 2 was risk factors to body weight loss during three months after gastrectomy in GC patients. However, the result was contract with the study by Park et al (2018) who found that preoperative BMI < 23 kg/m 2 were associated with severe weight loss after gastrectomy . Similar to previous studies (Davis et al, 2016;Nishigori et al, 2017;Segami et al, 2018), we found that total gastrectomy was a risk factor for postoperative weight loss.…”
Section: Factors Contributed To Body Weight Change After Gastrectomymentioning
confidence: 59%